Respuesta :
First minus -6 on both sides, then we would have -2 = -2x
Then divide both sides by -2 and then x=1 because negative divided by a negative is a positive.
Then divide both sides by -2 and then x=1 because negative divided by a negative is a positive.
4=−2x+6
Step 1: Flip the equation.
−2x+6=4
Step 2: Subtract 6 from both sides.
−2x+6−6=4−6−2x=−2
Step 3: Divide both sides by -2.
−2x−2=−2−2x=1
Answer:x=1
hope this helps you! :)
Step 1: Flip the equation.
−2x+6=4
Step 2: Subtract 6 from both sides.
−2x+6−6=4−6−2x=−2
Step 3: Divide both sides by -2.
−2x−2=−2−2x=1
Answer:x=1
hope this helps you! :)